2016
DOI: 10.15330/cmp.8.2.215-223
|View full text |Cite
|
Sign up to set email alerts
|

The vertex Zagreb indices of some graph operations

Abstract: Recently, Tavakoli et al. introduced a new version of Zagreb indices, named as vertex Zagreb indices. In this paper explicit expressions of different graphs operations of vertex Zagreb indices are presented and also as an application, explicit formulas for vertex Zagreb indices of some chemical graphs are obtained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…• The product of networks are mostly used in CGT for chemical structures such as carbonnano tube, bottleneck graph, linear polyomino chain, fence, closed fence, alkane and cyclohexane ( [1], [8], [13], [46]).…”
Section: Uses and Significance For Product Of Networkmentioning
confidence: 99%
“…• The product of networks are mostly used in CGT for chemical structures such as carbonnano tube, bottleneck graph, linear polyomino chain, fence, closed fence, alkane and cyclohexane ( [1], [8], [13], [46]).…”
Section: Uses and Significance For Product Of Networkmentioning
confidence: 99%
“…e author of [35] computed the forgotten topological index of different corona products of graphs, and the authors of [36] gave the exact expressions of Zagreb indices of the generalized hierarchical product of graphs. For more discussion and results, we refer to [37,38].…”
Section: Introductionmentioning
confidence: 99%
“…In [16], Das et al found some upper bounds for multiplicative Zagreb indices of some graph operations and Azari et al in [17], derived explicit formulae for computing the eccentric-distance sum of different graph operations. Recently, De computes the vertex Zagreb indices of different graph operations in [18]. For more results, interested readers are referred to the papers [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%